Energy efficient facile extraction process of cellulose nanofibres and their dimensional characterization using light scattering techniques. (1st June 2017) - Yadav, Chandravati; Saini, Arun; Maji, Pradip K.
Highlights: Extraction of cellulose nanofibres (CNFs) using mild chemi-mechanical approach. Organic solvent assisted in CNFs extraction at lower sonication power of 400 W. Dimensional analysis of CNFs through microscopic and light scattering techniques. Molecular weight and shape analysis of CNFs by static light scattering technique. Abstract: A chemi-mechanical approach was used to extract cellulose nanofibres (CNFs) from waste mango wood scraps using a mild chemical treatment ensuring no acid hydrolysis. The dimensional analysis for CNFs has been done by taking into account both the microscopic and light scattering techniques. The FESEM (field emission scanning electron microscopy) analysis revealed the diameter of obtained CNFs in the range of 5–40 nm with an average diameter of approximately 12 nm. The AFM (atomic force microscopy) analysis gave a more precise average diameter value of 5 nm for the obtained CNFs. The aspect ratio as determined by applying mathematical calculations on the data revealed through dynamic and static light scattering techniques (DLS, SLS) was approximately 200. The characteristic shape determined by fractal dimension investigation from SLS measurement revealed the rod/thread like shape of CNFs at lower concentrations.